2020
DOI: 10.1038/s41598-020-67022-5
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Gray Matter Changes in Patients with Type 2 Diabetes Mellitus

Abstract: Patients with Type 2 diabetes mellitus (T2DM) show cognitive and mood impairment, indicating potential for brain injury in regions that control these functions. However, brain tissue integrity in cognition, anxiety, and depression regulatory sites, and their associations with these functional deficits in T2DM subjects remain unclear. We examined gray matter (GM) changes in 34 T2DM and 88 control subjects using high-resolution T1-weighted images, collected from a 3.0-Tesla magnetic resonance imaging scanner, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 66 publications
(49 reference statements)
7
57
0
1
Order By: Relevance
“…This structure was already reported to present impaired neurovascular coupling in an fMRI study with the same cohort [Duarte et al, 2015]. As previously highlighted [Moran et al, 2013; Roy et al, 2020], lower regional GM volume in type 2 diabetes was also observed in our study in the limbic lobe, namely in the cingulate cortex and bilateral parahippocampal gyrus. Furthermore, there was a concomitant GM volume reduction and cortical thinning of the parahippocampal gyrus.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This structure was already reported to present impaired neurovascular coupling in an fMRI study with the same cohort [Duarte et al, 2015]. As previously highlighted [Moran et al, 2013; Roy et al, 2020], lower regional GM volume in type 2 diabetes was also observed in our study in the limbic lobe, namely in the cingulate cortex and bilateral parahippocampal gyrus. Furthermore, there was a concomitant GM volume reduction and cortical thinning of the parahippocampal gyrus.…”
Section: Discussionsupporting
confidence: 89%
“…These results are in accordance with previous studies of brain atrophy using VBM [Moran et al, 2013; Moulton et al, 2015; Wang et al, 2014] and cortical thickness [Brundel et al, 2010; Chen et al, 2015; Chen et al, 2017; Li et al, 2018; Shi et al, 2019] analysis in diabetic populations. In our study, decreased regional GM volumes appeared in several regions in type 2 diabetes patients, mainly in the frontal lobe, as in [Moran et al, 2013; Moulton et al, 2015; Roy et al, 2020], and sub-lobar cortex. Specifically, we observed decreased GM volume in different clusters of the insula, which has been implicated in an overwhelming variety of functions ranging from sensory processing to representation of feelings and emotions [Roy et al, 2020].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, there is no research on the relationship between changes in intra-SN functional connectivity (FC) and cognitive function in patients with T2DM. Although multiple neuroimaging studies (Liu et al, 2017;Wu et al, 2017;Roy et al, 2020) have found that gray matter (GM) volume (GMV) atrophy in the SN core region (insula) is related to cognitive function, the results of research examining functional changes in the SN are not consistent in patients with T2DM. Research using restingstate functional magnetic resonance imaging (fMRI) found that neuronal activity increases in the anterior cingulate cortex of patients with T2DM (Liu et al, 2016), the degree centrality of the right insula and the dorsal anterior cingulate increase, and FC is enhanced (Cui et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The cerebellum has traditionally been considered a stable area against the damage of diabetic hyperglycemia (15), but recent neuroimaging studies have challenged this view. Structural MR studies have shown that cerebellar gray matter (GM) is atrophic in patients with T2DM (16)(17)(18). Diffusion tensor imaging (DTI) studies have shown that the white matter microstructure of posterior cerebellar and cerebralcerebellar white matter connections are decreased in T2DM patients (19,20).…”
Section: Introductionmentioning
confidence: 99%